DEREGULATION, SAVINGS, CREDIT TO PRIVATE SECTOR AND ECONOMIC GROWTH IN NIGERIA: AN ARDL-BOUND TESTING APPROACH - Obiwuru, Timothy Chidi; Okwu, Andy Titus; Ofoegbu, Donald Ikenna (European Scientific Journal, ESJ, 2012)
The objective of the study was to assess the impact of financial sector deregulation reforms on savings, credit to private sector, and the economic growth of Nigeria from 1970 to 2009. Upon investigation of the long run and short run impact of financial deregulation on the selected macroeconomic variables, using the ARDL-bound test approach, it was discovered, that in both long and short run, financial deregulation had no significant impact on the real interest rate, and if any, its effect suggest a negative; therefore not in conformity with the McKinnon-Shaw hypothesis, that suggest that deregulation of the financial system enhances competition in the system and therein causes interest rate to be positive. However, increases in savings and the credit to private sector observed in the study, can hardly be attributed to financial deregulation (or the real interest rate) as its effect in the short run were minimally positive, and utterly negative in the long-run. The same effect was evidence in the economic growth variable. The study therefore concluded that the shifting effects from positive in the short run to negative in the long run, is attributable to lack of continuity in the implementation of financial deregulation reforms and absence of competition in the industry. All in all, financial deregulation did not induce positive real interest rate (to encourage savings). Suggesting that, interest rate on deposit has not been the major factor that propelled depositors to save in Nigeria, but rather the lack of investment alternatives outside financial assets.